Comparison of the DNDC, LandscapeDNDC and IAP-N-GAS models for simulating nitrous oxide and nitric oxide emissions from the winter wheat–summer maize rotation system. (November 2015) - Zhang, Wei; Liu, Chunyan; Zheng, Xunhua; Zhou, Zaixing; Cui, Feng; Zhu, Bo; Haas, Edwin; Klatt, Steffen; Butterbach-Bahl, Klaus; Kiese, Ralf
Abstract: The DNDC, LandscapeDNDC and IAP-N-GAS models have been designed to simulate the carbon and nitrogen processes of terrestrial ecosystems. Until now, a comparison of these models using simultaneous observations has not been reported, although such a comparison is essential for further model development and application. This study aimed to evaluate the performance of the models, delineate the strengths and limitations of each model for simulating soil nitrous oxide (N2 O) and nitric oxide (NO) emissions, and explore short-comings of these models that may require reconsideration. We conducted comparisons among the models using simultaneous observations of both gases and relevant variables from the winter wheat–summer maize rotation system at three field sites with calcareous soils. Simulations of N2 O and NO emissions by the three models agreed well with annual observations, but not with daily observations. All models failed to correctly simulate soil moisture, which could explain some of the incorrect daily fluxes of N2 O and NO, especially for intensive fluxes during the growing season. Multi-model ensembles are promising approaches to better simulate daily gas emissions. IAP-N-GAS underestimated the priming effect of straw incorporation on N2 O and NO emissions, but better results were obtained with DNDC95 and LandscapeDNDC. LandscapeDNDC and IAP-N-GAS need to improve the simulation of irrigation water allocation and residue decomposition processes, respectively, and together to distinguish different irrigation methods as DNDC95 does. All three models overestimated the emissions of the nitrogenous gases for high nitrogen fertilizer (>430 kg N ha −1 yr −1 ) addition treatments, and therefore, future research should focus more on the simulation of the limitation of soil dissolvable organic carbon on denitrification in calcareous soils. Highlights: Incorrect soil moisture simulations explain some incorrect daily flux estimations. Multi-model ensembles are beneficial for better simulating daily gas emissions. All models should focus on the carbon-limit on denitrification in calcareous soil. LandscapeDNDC needs to modify the allocation of irrigation water. LandscapeDNDC and IAP-N-GAS need to distinguish irrigation method.